2022
DOI: 10.1111/tbed.14583
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Lumpy skin disease virus isolated from a giraffe in Vietnam

Abstract: While investigating a giraffe's death in a Vietnamese zoo, we successfully identified and isolated Lumpy skin disease virus (LSDV) from skin nodule biopsies and ruptured nodule wound swab samples. Phylogenetic analysis indicated that the isolate obtained in this study was closely related to the previous Vietnamese and Chinese LSDV strains from cattle. This is the first report on the genome detection and isolation of LSDV in a diseased giraffe in Vietnam. Further study is needed to better understand the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…has also been reported to be susceptible [9]. Besides, wildlife can also be susceptible, and a recent report described clinical diseases and deaths of giraffes in a Vietnamese zoo [29]. Previously, the susceptibility of springbok, impala, and giraffe to the virus has been experimentally documented [14,30].…”
Section: Host Range Morbidity and Mortality Ratesmentioning
confidence: 99%
“…has also been reported to be susceptible [9]. Besides, wildlife can also be susceptible, and a recent report described clinical diseases and deaths of giraffes in a Vietnamese zoo [29]. Previously, the susceptibility of springbok, impala, and giraffe to the virus has been experimentally documented [14,30].…”
Section: Host Range Morbidity and Mortality Ratesmentioning
confidence: 99%
“…The vulnerability of impala, giraffe and springbok to the LSDV has been confirmed (Young et al 1970;Lamien et al 2011a). Dao et al (2022) identified and characterized the LSDV from a giraffe (Giraffa camelopardalis) in Vietnam. Specific antibodies to LSDV have previously been reported in wildlife, such as African buffalo (Syncerus caffer), Arabian oryx (Oryx leucoryx), blue wildebeest (Connochaetes taurinus), giraffe, eland (Taurotragus oryx), greater kudu and impala (Davies 1982;Hedger and Hamblin 1983;Greth et al 1992;Barnard 1997;Fagbo et al 2014;Molini et al 2021).…”
Section: Morbidity Mortality and Risk Factorsmentioning
confidence: 93%
“…These results are applicable only for the Neethling attenuated vaccination. Azeem et al (2022), the role of wildlife in the spread of the LSD is not yet clear, however, various studies proposed that wild animals may play an active part in the spread of LSD (Dao et al 2022). Seropositivity in wild animals shows the possibility in spreading the LSD (Namazi and Tafti 2021).…”
Section: Morbidity Mortality and Risk Factorsmentioning
confidence: 99%
“…The main hosts of the first two viruses are sheep and goat, while the LSDV mainly affects the cattle and water buffalo ( Afonso et al, 2012 ; Fagbo et al, 2014 ; Lefkowitz et al, 2018 ). In addition, LSDV can also infect giraffes, impalas, and wildebeest ( Young et al, 1970 ; Dao et al, 2022 ). Capripoxvirus genus is the most harmfully significant in the Poxviridae family affecting domestic ruminants in Africa and Asia.…”
Section: Etiologymentioning
confidence: 99%